The impact of industry specialist audit firms on pricing of discretionary accruals and earnings management: Australian evidence - Singh, Harj; Khoo, M. (Virtus Interpress, 2012)
This paper examines the relationship between the capital market pricing of Australian publicly listed firms and earnings management (proxied by discretionary accruals) during a three-year pooled timeframe of 2008 to 2010. More importantly, the role of industry specialist audit firms on market returns and earnings management relationship is investigated. Main results indicate a significant negative relationship between firm returns and earnings management. However, there is no significance in the role of industry specialist audit firms on the firm returns and earnings management linkage. On the other hand, sensitivity tests indicate that industry specialist audit firms play in significant monitoring role for audit committees with less than fifty percent of their members classified as independent. One major contribution is for regulators (aiming to improve audit quality) to strengthen key firm-level corporate governance mechanisms. Specifically, by placing the consequences from this paper into perspective, there may be a greater likelihood of increased audit quality by altering audit committee's structure, composition and authority levels.